2005
DOI: 10.1074/jbc.m411324200
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Transmembrane Regions to ATP-gated P2X2 Channel Permeability Dynamics

Abstract: ATP-gated P2X 2 channels undergo activation-dependent permeability increases as they proceed from the selective I 1 state to the I 2 state that is readily permeable to organic cations. There are two main models about how permeability changes may occur. The first proposes that permeability change-competent P2X channels are clustered or redistribute to form such regions in response to ATP. The second proposes that permeability changes occur because of an intrinsic conformational change in P2X channels. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 57 publications
10
89
0
Order By: Relevance
“…1G). Our data for WT P2X 2 reproduce past work with P2X 2 (2,4,6,19) and allowed us to determine whether Panx-1 and CBX affected NMDG ϩ permeability. We found that the shift in NMDG ϩ E rev was identical from cells expressing WT P2X 2 , P2X 2 with Panx-1, or P2X 2 with CBX (ϩ19 Ϯ 2, ϩ20 Ϯ 2, and ϩ19 Ϯ 2 mV, respectively; n ϭ 10, 9, and 8) (Fig.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…1G). Our data for WT P2X 2 reproduce past work with P2X 2 (2,4,6,19) and allowed us to determine whether Panx-1 and CBX affected NMDG ϩ permeability. We found that the shift in NMDG ϩ E rev was identical from cells expressing WT P2X 2 , P2X 2 with Panx-1, or P2X 2 with CBX (ϩ19 Ϯ 2, ϩ20 Ϯ 2, and ϩ19 Ϯ 2 mV, respectively; n ϭ 10, 9, and 8) (Fig.…”
Section: Resultssupporting
confidence: 71%
“…1 A). The second model posits that the I 2 state is an intrinsic property of P2X receptors involving slow conformational changes that allow organic cations to flow (2)(3)(4)(5)(6)19). We call this the ''gating model'' (Fig.…”
mentioning
confidence: 99%
“…PCR amplification included denaturation at 96°C for 5 min, 48 cycles at 94°C for 45 s, 58°C for 45 s, and 72°C for 90 s, followed by 72°C for 10 min. Samples (10 µl) of PCR product were analyzed by methods have been described in detail previously (Eickhorst et al, 2002;Khakh and Egan, 2005).…”
Section: Qualitative Reverse Transcription (Rt)-pcr Analysis Of Tlr4mentioning
confidence: 99%
“…Functions of the TM domains in channel gating have been deeply studied, and its roles in pore location, ion permeability and structural rearrangements were confirmed by crystal structures [88][89][90][91][92][93][94][95][96][97] . Under normal conditions, pore opening of P2X receptors is controlled by ATP binding.…”
Section: N-and C-terminimentioning
confidence: 99%